The Saudi Abnormal Glucose Metabolism and Diabetes Impact Study (SAUDI-DM) - Al-Rubeaan, Khalid (Ann Saudi Med, 2014)
BACKGROUND AND OBJECTIVES: Saudi Arabia underwent opulence-driven socio-cultural and lifestyle changes leading to soaring rates of diabetes mellitus. This study exposes the epidemiology of abnormal glucose metabolism namely: diabetes and impaired fasting glucose (IFG) in 13 administrative regions of Saudi Arabia. DESIGN AND SETTINGS: This is a nationwide, household, population-based cross-sectional study that was conducted through primary health care centers during the period 2007–2009. PATIENTS AND METHODS: A nationwide, household, population-based cohort of 53 370 participants aged 0–100 years adjusted to be compatible with population census was interviewed and anthropometric measures were collected. Fasting blood sample was used to screen for IFG and diabetes. RESULTS: The overall prevalence of abnormal glucose metabolism was 34.5%, which included 22.6% patients with IFG, 11.9% patients with diabetes, and 6.2% patients who unaware of their disease. Diabetes prevalence was 40.2% for subjects aged ≥45 years and 25.4% for those aged ≥30 years that decreased to 11.9% when the full age spectrum was considered. Type 1 diabetes prevalence was 0. 8%, contributing only to 6.6% of the total population of patients with diabetes. The top 5 regions with the highest abnormal glucose metabolism prevalence were Makkah (43.4%), Aljouf (41.7%), Eastern region (37.16%), Madinah (35.4%), and Qassim (33.7%). Urbanization, age, and obesity were behind the wide variations in diabetes and IFG prevalence in the 13 regions. CONCLUSION: Abnormal glucose metabolism has reached an epidemic state in Saudi Arabia, where one-third of the population is affected and half of diabetic cases were unaware of their disease. This observation warrants an urgent strategy for launching diabetes primary prevention and screening programs.